2018
DOI: 10.20319/pijss.2017.32.24582472
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Reported Influence of Using SMS Language in Texting and Social Media on Saudi Students' Academic Writing

Abstract: SMS language is a form of written English that is often used in informal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Moreover, the excessive use of mobile apps is leading students to use unstandardized short abbreviations and incorrect spellings [12], [39], poor punctuation and grammatical errors [13]. In a study of the influence of mobile texting language on Saudi students' academic writing, Alharbi [40] indicated that students always make spelling and sentence construction errors in formal writing due to their overreliance on the language used on mobile texting apps.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Moreover, the excessive use of mobile apps is leading students to use unstandardized short abbreviations and incorrect spellings [12], [39], poor punctuation and grammatical errors [13]. In a study of the influence of mobile texting language on Saudi students' academic writing, Alharbi [40] indicated that students always make spelling and sentence construction errors in formal writing due to their overreliance on the language used on mobile texting apps.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Students found the application more interesting because they could choose different versions of keyboards and receive suggestions for vocabulary. Another study examined the influence of mobile typing apps, such as SMS message apps, on undergraduate students' writing skills in Pakistan [36]. They noted that this usage negatively influenced students' academic writing skills, especially in spelling.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization has profoundly changed the way in which news and opinions circulate, enabling everyone to talk one-to-many and basically allowing people to bypass any kind of media (Alharbi B. 2017 andAli S. 2017).…”
Section: Introductionmentioning
confidence: 99%